Formal Algebraic Specification of an IoT/Fog Data Centre for Fat Tree or Leaf and Spine architectures - Juan Roig, Pedro; Alcaraz, Salvador; Gilly, Katja; Filiposka, Sonja; Aknin, Noura (IEEE, 2020)
Fog computing is an evolution of cloud computing paradigm, whose key point is the location of computing resources at the edge of the network. Data center facilities at the fog level are smaller than those at the cloud level, but nevertheless, they may share similar topologies, such as fat tree or leaf and spine architectures. In this paper, a formal algebraic specification of an IoT/Fog environment based on each of both architectures is presented, where users may be moving around and their associated computing assets are meant to migrate among hosts in order to follow their respective users so as to be as close as possible to them.
Keywords: ACP, fog computing, IoT, formal protocol specification, networking